Exploring the impact of technological innovation, environmental regulations and urbanization on ecological efficiency of China in the context of COP21. (15th November 2020) - Yasmeen, Humaira; Tan, Qingmei; Zameer, Hashim; Tan, Junlan; Nawaz, Kishwar
Abstract: The objective of this study was to explore the roles of technological innovation, environmental regulations, and urbanization in ecological efficiency within the context of the 2015 Paris agreement. Initially, the study employed the super-efficiency DEA model to estimate the ecological efficiencies of 30 regions in China. Following this, the system GMM method was used to explore the impacts of technological innovation, environmental regulations, and urbanization on ecological efficiency. We used annual data from 2008 to 2018. The results indicate that, in terms of ecological efficiency, the eastern region was the highest ranked, followed by central and western regions, respectively. The urbanization index has a negative impact on ecological efficiency at a national level. However, in the context of regions, it is positively significant in the eastern region, while the results in the central and western regions are insignificant. The influence of technological innovation on ecological efficiency is found to be significantly positive at both national and regional levels. It is generally perceived that environmental regulations are pivotal for sustainability. Our results verify this argument and indicate that environmental regulations have a positive impact on ecological efficiency in the central and eastern regions. However, their impact is found to be negative in the western region. Policy suggestions are discussed, in order to further strengthen environmental laws and sustainability. Graphical abstract: Image 1 Highlights: Super Efficiency DEA and System GMM methods are used. Environmental regulations are essential for sustainability. Technological innovation can play a pivotal role toward ecological efficiency. Eastern region is found high ecological efficient compared with other regions.